Safety study on novel ayurvedic nutritive powder - An experimental study - Vinuta Kulkarni; Rudramma R Hiremath; Sreenivasa Prasad Buduru; Veena Babu Kupati (Wolters Kluwer Medknow Publications, 2021)
Introduction: It has been estimated that in India, 65%, i.e., nearly 80 million children under 5 years of age suffer from varying degrees of malnutrition. Most of the children fall into the pit of Malnutrition during the weaning phase. Mothers are expected to make this "weaning Bridge." This includes utilization of "Supplementary Feeding Programs." Many weaning foods are available which claims the specific dietary implementation. The development of a nutritive Powder in weaning children is need of hour. This study includes safety of novel Ayurvedic nutritive powder in Wistar rat pups. Aim: This study aims to evaluate its safety in experimental animals. Materials and Methods: Ingredients selected were Mudga, Godhuma, Rakta Shali, Ragi, Trikatu, Yastimadhu, and Khanda Sharkara. Safety study of Nutritive Powder was done in 20 days old Wistar Rat pups for 90 days. Parameters selected are HISTOPATHOLOGICAL study and biochemical investigations. Results: No mortality and abnormal behavioral changes were found in rat pups during experimental study. No remarkable pathological changes were observed. Biochemical Parameters revealed significant decrease in blood sugar, serum urea, and alkaline phosphatase in test group when compared to control. Conclusion: Nutritive powder when administered in the dose of 40 g/Kg body weight of animal for 90 days. No mortality was seen in any animals of test group. No remarkable pathological changes were seen in histopathological study of liver and kidney. Significant decrease of blood glucose, serum urea serum alkaline phosphatase was seen in test group animals compared to control group animals.